Sosialisasi Pentingnya Penyusunan Laporan Keuangan serta Pelatihan Penyusunan Laporan Pajak pada Industri Kecil Menengah TS Aluminium di Kelurahan Sorosutan - Winda Fadhilla Maulidya; Ulinnuha Yudiansa Putra (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Sorosutan is a village located in Umbulharjo sub-district, Yogyakarta, Special Region of Yogyakarta. In the Sorosutan area, there are approximately 77 small and medium metal industries (IKM), one of which is TS Aluminum. TS Aluminum is a small and medium industry which is engaged in aluminum metal casting. TS Aluminum is divided into several productions, namely, among others, the production of frying pans, the production of cake molds with 15 different production houses. There are also approximately 15 partners under the auspices of TS Aluminum, where TS Aluminum itself provides the supply of raw materials and then the partners make their own products. The existence of these various partners, of course, requires the preparation of financial statements and the preparation of correct tax reports and in accordance with applicable regulations so that business actors can know their financial condition and the business they are running can survive. The community service activities carried out include training and socialization regarding the importance of preparing financial reports and tax reporting. The implementation of this training and socialization is expected to make it easier for small and medium industry players to prepare financial reports and tax reports so as to improve the financial quality of these small and medium industries.